Can time-dependent density functional theory predict intersystem crossing in organic chromophores? A case study on benzo(bis)-X-diazole based donor–acceptor–donor type molecules. Issue 24 (6th June 2017) - Tam, Teck Lip Dexter; Lin, Ting Ting; Chua, Ming Hui
Abstract : Here we utilized new diagnostic tools in time-dependent density functional theory to explain the trend of intersystem crossing in benzo(bis)-X-diazole based donor–acceptor–donor type molecules. Abstract : Here we utilized new diagnostic tools in time-dependent density functional theory to explain the trend of intersystem crossing in benzo(bis)-X-diazole based donor–acceptor–donor type molecules. These molecules display a wide range of fluorescence quantum yields and triplet yields, making them excellent candidates for testing the validity of these diagnostic tools. We believe that these tools are cost-effective and can be applied to structurally similar organic chromophores to predict/explain the trends of intersystem crossing, and thus fluorescence quantum yields and triplet yields without the use of complex and expensive multireference configuration interaction or multireference pertubation theory methods.